2013
DOI: 10.4155/bio.12.304
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Critical Reagents in Ligand-Binding Assays: Enabling Robust Bioanalytical Methods and Lifecycle Management

Abstract: The effective management of validated ligand-binding assays used for PK, PD and immunogenicity assessments of biotherapeutics is vital to ensuring robust and consistent assay performance throughout the lifetime of the method. The structural integrity and functional quality of critical reagents is often linked to ligand-binding assay performance; therefore, physicochemical and biophysical characterization coupled with assessment of assay performance can enable the highest degree of reagent quality. The implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…61,[64][65][66] So-called signal generating reagents (SGR) 67 are analytebinding molecules tagged to some sort of reporter, such as an enzyme, a dye, fluorophore, or hapten group to enable downstream detection of the binding event. 69,70 Reduction of background signals can be obtained by minimization of non-specific SGR binding through careful choice of reagents, extensive blocking, and, in some cases, by sample dilution (see below). For example, it has been demonstrated that PCR-based signal amplification enabled the use of weak binders which were not well suited for conventional ELISA.…”
Section: General Aspectsmentioning
confidence: 99%
“…61,[64][65][66] So-called signal generating reagents (SGR) 67 are analytebinding molecules tagged to some sort of reporter, such as an enzyme, a dye, fluorophore, or hapten group to enable downstream detection of the binding event. 69,70 Reduction of background signals can be obtained by minimization of non-specific SGR binding through careful choice of reagents, extensive blocking, and, in some cases, by sample dilution (see below). For example, it has been demonstrated that PCR-based signal amplification enabled the use of weak binders which were not well suited for conventional ELISA.…”
Section: General Aspectsmentioning
confidence: 99%
“…Reagent characteristics can include but are not limited to the following: identity, source, purity, concentration (or titer), binding affinity, isotype (monoclonal/polyclonal antibody), molecular weight, specificity, incorporation ratio, and aggregation level. Several recent publications discuss in detail critical reagent characterization and testing methods (5,6,10).…”
Section: Characterization and Qualification Of Critical Reagentsmentioning
confidence: 99%
“…Reagent screening/pairing The quality of critical reagents, for example, specificity, selectivity and consistency between batches, is essential for the good performance of all LBA-based bioanalytical methods for supporting biologics [8][9][10][11]. The rapid generation and selection of these reagents such as anti-idiotypic ('anti-Id') antibodies often form the primary start point of the critical path of method development.…”
Section: Applications For Laboratory Automationmentioning
confidence: 99%